Comparative study of anaphors between Xitsonga and English - Masina, Millicent (My University, 2022)
The aim of this study was to compare anaphors between Xitsonga and English. This study was to find out if there are any similarities and differences of anaphors between Xitsonga and English. The researcher also wanted to find the functions of anaphors in Xitsonga and English, the types of anaphors, as well as surface structures and deep structures of anaphors in Xitsonga and English. The researcher looked at the syntax of Xitsonga and English focusing on anaphors. The similarities and differences were discovered, the types of anaphors in Xitsonga and English, the functions of anaphors in Xitsonga and English, as well as the surface structure and the deep structure of anaphors in Xitsonga and English were compared. The interpretation and meaning of anaphors are the same but varies in syntax constructions. The findings of the study are that there are two types of anaphors in Xitsonga and in English, which are reflexives and reciprocals. In Xitsonga, prefixes of verbs form reflexivity, for example ‘tirhandza’ (loves herself). The prefix ti- from the verb tirhandza forms reflexivity. On the other hand, reciprocals are formed by suffixes, for example; ‘rhandzana’ (love each other). The suffix -ana from the verb rhandzana form reciprocity. This means anaphors in Xitsonga are formed by verbs. English uses pronouns like ‘himself’, ‘herself’ and ‘themselves’ to identify their anaphors. The study suggests that scholars must do further research on anaphors between Xitsonga and English. Academics, linguists among others, must be interviewed as they may have better interpretation of anaphors between Xitsonga and English.
Thesis (M.A. (Translation and Linguistics)) -- University of Limpopo, 2022
Keywords: Comparative study; Anaphors; Xitsonga; English; Interpretation; Similarities; Differences; English language -- Reciprocals; English language -- Reflexives; Tsonga language -- Reciprocals; Tsonga language -- Reflexives; Grammar, Comparative and general -- Reciprocals; Grammar, Comparative and general -- Reflexives